Synthesis of the stationary-phase sigma factor sigma s is positively regulated by ppGpp. - Gentry, D R (1993)
Strains of Escherichia coli which lack detectable guanosine 3',5'-bispyrophosphate (ppGpp) display a pleiotropic phenotype that in some respects resembles that of rpoS (katF) mutants. This led us to examine whether ppGpp is a positive regulator of sigma s synthesis. sigma s is a stationary-phase-specific sigma factor that is encoded by the rpoS gene. We found that a ppGpp-deficient strain is defective in sigma s synthesis as cells enter stationary phase in a rich medium, as judged by immunoblots. Under more-defined conditions we found that the stimulation of sigma s synthesis following glucose, phosphate, or amino acid starvation of wild-type strains is greatly reduced in a strain lacking ppGpp. The failure of ppGpp-deficient strains to synthesize sigma s in response to these starvation regimens could indicate a general defect in gene expression rather than a specific dependence of rpoS expression on ppGpp. We therefore tested the effect of artificially elevated ppGpp levels on sigma s synthesis either with mutations that impair ppGpp decay or by gratuitously inducing ppGpp synthesis with a Ptac::relA fusion. In both instances, we observed enhanced sigma s synthesis. Apparently, ppGpp can activate sigma s synthesis under conditions of nutrient sufficiency as well as during entry into stationary phase. This finding suggests that changes in ppGpp levels function both as a signal of imminent stationary phase and as a signal of perturbations in steady-state growth.